2011
DOI: 10.1177/0269216311402713
|View full text |Cite
|
Sign up to set email alerts
|

Illicit drug use as a challenge to the delivery of end-of-life care services to homeless persons: Perceptions of health and social services professionals

Abstract: Homeless persons tend to die younger than the housed population and have complex, often unmet, end-of-life care needs. High levels of illicit drug use among this population are a particular challenge for health and social services professionals involved in end-of-life care services delivery. This article explores the challenges of end-of-life care services to homeless illicit drug users based on data collected during a national study on end-of-life care services delivery to homeless persons in Canada. The auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
121
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(122 citation statements)
references
References 51 publications
1
121
0
Order By: Relevance
“…Among homeless parolees, multiple challenges with mental health issues, substance use addiction, unemployment, and unstable housing conditions impact successful re-entry (Binswanger et al, 2011). Illicit drug use is a contributing factor to incarceration as well as homelessness (McNeil & Guirguis-Younger, 2012; Tsai, Kasprow, & Rosenheck, 2013). However, recently released offenders continue to have unmanaged drug issues, with probationers and/or parolees affected four to nine times higher when compared to their non-supervised counterparts (Fearn et al, 2016).…”
mentioning
confidence: 99%
“…Among homeless parolees, multiple challenges with mental health issues, substance use addiction, unemployment, and unstable housing conditions impact successful re-entry (Binswanger et al, 2011). Illicit drug use is a contributing factor to incarceration as well as homelessness (McNeil & Guirguis-Younger, 2012; Tsai, Kasprow, & Rosenheck, 2013). However, recently released offenders continue to have unmanaged drug issues, with probationers and/or parolees affected four to nine times higher when compared to their non-supervised counterparts (Fearn et al, 2016).…”
mentioning
confidence: 99%
“…No additional studies were found through contacting authors of eligible studies. The study by Neil et al [3638] was reported in more than one paper focusing on different aspects of the data, as was the study by Ko et al [32, 33] and also by Song et al [39, 40]. No studies were excluded following quality assessment because none were found to be of very poor standard (Table 3 of Appendix 1).…”
Section: Resultsmentioning
confidence: 99%
“…Often shaped by discrimination, disrespect [6] and disempowerment [42]. As a result, expectations and conceptualisation of health care, including of palliative care, described by homeless people appear different to those perhaps commonly shared by the housed population [6, 33, 34, 36, 40]. This contributes to the difficulty homeless people had in trusting or engaging with health and social services [6, 9, 3437, 39] as outlined in the quote below:

“There is a lot of shame….low self-esteem, horrific histories of trauma and abuse, mistrust of caregivers.

…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, while homeless populations have high levels of alcohol and/or illicit drug use, palliative care services typically operate under abstinence-only policies that constrain access to care (McNeil and Guirguis-Younger 2012). Accordingly, homeless persons are typically unable to access much needed care at the end of life, often dying alone and unsupported .…”
Section: Lessons Learned and Future Directionsmentioning
confidence: 99%
“…Recently, Canadian researchers have advanced a definition of homelessness that recognizes this diversity by situating homelessness along a continuum of living arrangements, including: (1) living outside or in places not fit forin-patient care (Hwang et al 2011;Palepu et al 1999), they frequently have unmet health needs due to the barriers that they face to accessing care and adhering to treatment (Hwang et al 2010;Khandor et al 2011;McNeil and Guirguis-Younger 2012). The reasons for this are complex and, to a great extent, largely the product of the challenges experienced by homeless persons.…”
mentioning
confidence: 99%